2022
DOI: 10.1186/s12891-021-04976-1
|View full text |Cite
|
Sign up to set email alerts
|

The accuracy of MRI in diagnosing and classifying acute traumatic multiple ligament knee injuries

Abstract: Background Magnetic resonance imaging (MRI) is widely used for the evaluation of knee injuries, however, the accuracy of MRI in classifying multiple ligament knee injuries (MLKIs) remains unknown. This study aimed to investigate the accuracy of MRI in diagnosing and classifying acute traumatic MLKIs, we hypothesize that MRI had high accuracy in detecting and classifying MLKIs. Methods The clinical data of 97 patients who were diagnosed with acute t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 21 publications
1
6
0
Order By: Relevance
“…According to our research, MRI demonstrated superior performance in assessing complex musculoskeletal injuries compared to CT and FAST in terms of sensitivity, specificity, PPV, NPV and overall accuracy. These results are consistent with those who emphasized the superiority of MRI in this regard 23,24 …”
Section: Discussionsupporting
confidence: 92%
“…According to our research, MRI demonstrated superior performance in assessing complex musculoskeletal injuries compared to CT and FAST in terms of sensitivity, specificity, PPV, NPV and overall accuracy. These results are consistent with those who emphasized the superiority of MRI in this regard 23,24 …”
Section: Discussionsupporting
confidence: 92%
“…This can often lead to diagnosis of MLKI being missed acutely and presenting in the chronic setting 66. Although the use of MRI is widely advocated, literature assessing the sensitivity and specificity of MRI in patients with MLKI is limited 67–73. Original data regarding the value of MRI are of levels II-III evidence 56 67 70 73 74.…”
Section: Resultsmentioning
confidence: 99%
“…Study by Li et al also showed male preponderance. 7 Madhusudhan et al showed that 68% were males and mean age was 52 years and majoirty cases had swelling as most common complaints. 9 Similar findings were seen by Ruth et al that MRI is highly accurate in diagnosing meniscal and anterior cruciate ligament (ACL) tears.…”
Section: Discussionmentioning
confidence: 99%
“…MRI was found to have high sensitivity (90.7%) and moderate specificity (63.6%) in the diagnosis of injuries to the ACL; high sensitivity (90.4%) and moderate specificity (50%) in the diagnosis of injuries to the PCL. 7 Siddiqui et al showed there were only marginal differences in sensitivity and specificity of clinical examination and MRI in diagnosis of lateral meniscal and ACL injury.…”
Section: Discussionmentioning
confidence: 99%